Outward FDI, location choices and innovation performance of emerging market enterprises - Piperopoulos, Panagiotis; Wu, Jie; Wang, Chengqi (Elsevier, 2018)
Although prior research conceptualizes how knowledge-seeking motivates the internationalization of emerging-market enterprises (EMEs), whether outward foreign direct investment (OFDI) indeed leads to enhanced innovation performance has received limited attention. We address this subject by conceptualizing how Chinese EMEs’ OFDI enhances their subsidiaries’ organizational learning and innovation performance and whether geographic location choices influence this relationship. Our panel data analysis of Chinese EMEs shows that OFDI has a positive effect on innovation performance of Chinese EMEs’ subsidiaries and that this effect is stronger when the OFDI is directed towards developed rather than emerging countries. These findings advance the notion that EMEs can use OFDI as a strategy to globalize R&D and enhance their innovation performance and demonstrate that certain established assumptions regarding organizational learning are not valid for EMEs.